Hope in a Democratic age : philosophy, religion, and political theory - Mittleman, Alan (Oxford University Press, 2009)
How and why should hope play a key role in a twenty-first century democratic politics? Alan Mittleman offers a philosophical exploration of the theme, contending that a modern construction of hope as an emotion is deficient. He revives the medieval understanding of hope as a virtue, reconstructing this in a contemporary philosophical idiom. In this framework, hope is less a spontaneous reaction than it is a choice against despair; a decision to live with confidence and expectation, based on a rational assessment of possibility and a faith in the underlying goodness of life. In cultures shaped b.